2017
DOI: 10.1159/000456072
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Vonoprazan for Proton Pump Inhibitor-Resistant Reflux Esophagitis

Abstract: Background: Vonoprazan (VPZ) is a novel potassium-competitive acid blocker that may be clinically beneficial for proton pump inhibitor (PPI)-resistant reflux esophagitis (RE). The aim of this study was to investigate the efficacies of VPZ therapy at 20 mg for 4 weeks in patients with PPI-resistant RE and VPZ maintenance therapy at 10 mg for 8 weeks in patients who have been successfully treated. Methods: Subjects comprised 24 patients with PPI-resistant RE (Los Angeles classification grade A/B/C/D: 3/7/11/3). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
69
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(88 citation statements)
references
References 17 publications
5
69
2
Order By: Relevance
“…The present study shows that vonoprazan 10 mg daily resulted in a 100% improvement and 83% resolution of the GERD symptoms in patients with erosions. A recent Japanese study reported an 88% (21/24) endoscopic healing rate by vonoprazan 20 mg daily for four weeks in patients with PPI-resistant reflux esophagitis (7). The healing rate is similar to the resolution rate of GERD symptom in the present study.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The present study shows that vonoprazan 10 mg daily resulted in a 100% improvement and 83% resolution of the GERD symptoms in patients with erosions. A recent Japanese study reported an 88% (21/24) endoscopic healing rate by vonoprazan 20 mg daily for four weeks in patients with PPI-resistant reflux esophagitis (7). The healing rate is similar to the resolution rate of GERD symptom in the present study.…”
Section: Discussionsupporting
confidence: 88%
“…The healing rate is similar to the resolution rate of GERD symptom in the present study. Baseline LA classifications were mainly grade B or greater (21/24, 88%) in their study (7) and 83% (5/6) in the present study. A moderate or severe LA grade may exist frequently in patients with PPI-resistant reflux esophagitis.…”
Section: Discussioncontrasting
confidence: 38%
See 1 more Smart Citation
“…Changes in the gastric pH after a single 20 mg administration of vonoprazan suggest that it is the optimal agent for on-demand therapy for reflux symptoms. Although the efficacy of vonoprazan for PPI-resistant RE has been reported [13, 14, 15], no results of on-demand therapy for mild RE using vonoprazan at 20 mg have been reported. Moreover, the problem of hypergastrinemia caused by long-term use of vonoprazan may be resolved by on-demand therapy.…”
Section: Introductionmentioning
confidence: 99%
“…The definition of PPI-resistant GERD should be modified after the launching of potent potassium-competitive acid blockers such as vonoprazan [43][44][45][46][47], the evaluation of other therapeutic agents for PPI-resistant GERD as monotherapy and add-on therapy to PPI or potassium-competitive acid blockers should be re-evaluated. One speaker talked about the efficacy of hangeshashinto for PPI-resistant reflux symptoms, while the other speaker talked about the efficacy of acotiamide for treating FD and other FGIDs (unpublished data).…”
Section: Core Symposium 3 Of the 13th Annual Meeting Of The Jga (2017)mentioning
confidence: 99%